PERAN ORANG TUA DALAM MENANGGULANGI KENAKALAN REMAJA DI KELURAHAN KEMBU DISTRIK KEMBU KABUPATEN TOLIKARA - Bas Weya, Dra. Evie A. A. Suwu, M.Si (Universitas Sam Ratulangi, 2015)
Teen delinquency problems until now can be said has become a social issue that must be confronted by the government, the community and family. Because adolescents and youth is the backbone of the nation so in penanggulangannya not easy to handle it must surely require various ways of handling. For forms of mischief teenagers cannot be tolerated as an ordinary misbehavior. According to the delinquency kartini kartono ( 2010 ) be called with the term juvenile delinquency is wicked behavior or worthless, or crime and delinquency young children, is a pain symptom socially ( pathological ) in children and teenagers caused by one form of social abandonment, so that they that develop the form of conduct which deviate. Matters of considerable prominence for the level of misbehavior a juvenile kelurahan Kembu include many making a fuss so that they deal with the security apparatus, a gunfight between community, memimum alcoholic beverages, smoking, and free sex. Economic issues especially economic parents who minimal has also determines the extent of the misbehavior teenagers. Aside from the issue of economic and environmental factors also involve affect an increase in teen misbehavior. In tackling misbehavior teenagers especially in kelurahan Kembu needs to be done the act of preventive and repressive. Keywords : teenagers, delinquency, juvenile